2007
DOI: 10.1074/jbc.m610648200
|View full text |Cite
|
Sign up to set email alerts
|

The c-Myc Target Gene Rcl (C6orf108) Encodes a Novel Enzyme, Deoxynucleoside 5′-monophosphate N-Glycosidase

Abstract: RCL is a c-Myc target with tumorigenic potential. Genome annotation predicted that RCL belonged to the N-deoxyribosyltransferase family. However, its putative relationship to this class of enzymes did not lead to its precise biochemical function. The purified native or N-terminal His-tagged recombinant rat RCL protein expressed in Escherichia coli exhibits the same enzyme activity, deoxynucleoside 5-monophosphate N-glycosidase, never before described. dGMP appears to be the best substrate. RCL opens a new rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
75
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 28 publications
7
75
0
Order By: Relevance
“…Inorganic pyrophosphatase catalyzes the reversible transfer of phosphoryl group from a polyphosphate to water and this reaction provides a thermodynamic pull for the synthesis of proteins and nucleic acids [33]. Deoxynucleoside 5'-monophosphate N-glycosidase catalyzes the hydrolysis of the N-glycosidic bond of the nucleotide to give deoxyribose 5-phosphate and a nucleobase, preferentially a purine [34]. The up-regulated inorganic pyrophosphatase and deoxynucleoside 5'-monophosphate N-glycosidase suggested the disturbance in nucleic acid metabolisms induced by Cd in D-shape larval mussels.…”
Section: Resultsmentioning
confidence: 99%
“…Inorganic pyrophosphatase catalyzes the reversible transfer of phosphoryl group from a polyphosphate to water and this reaction provides a thermodynamic pull for the synthesis of proteins and nucleic acids [33]. Deoxynucleoside 5'-monophosphate N-glycosidase catalyzes the hydrolysis of the N-glycosidic bond of the nucleotide to give deoxyribose 5-phosphate and a nucleobase, preferentially a purine [34]. The up-regulated inorganic pyrophosphatase and deoxynucleoside 5'-monophosphate N-glycosidase suggested the disturbance in nucleic acid metabolisms induced by Cd in D-shape larval mussels.…”
Section: Resultsmentioning
confidence: 99%
“…Construction of the Rcl Mutants-RclE93A, Rcl D69A, and Rcl D69N were previously described in Ghiorghi et al (9) and Yang et al (13) respectively. Oligonucleotides ϩ (Y13Aϩ, Y13Fϩ, S17Aϩ, S17Eϩ, R19Aϩ, H45Aϩ, S87Aϩ, S87Dϩ, E93Qϩ, S117Aϩ, S117Nϩ) and T7term, oligonucleotides Ϫ (Y13AϪ, Y13FϪ, S17AϪ, S17EϪ, R19AϪ, H45AϪ, S87AϪ, S87DϪ, E93QϪ, S117AϪ, S117NϪ) and T7prom (Table 1) were used in two separate PCR reactions using plasmid pET28aRcl as DNA template.…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that Rcl is a 2Ј-deoxynucleoside 5Ј-phosphate N-hydrolase that had not been previously described (9). Rcl hydrolyzes 2Ј-deoxyribonucleoside 5Ј-monophosphate (dNMP) 4 to form a free nucleobase moiety (N) and 2-deoxyribose 5-phosphate.…”
mentioning
confidence: 96%
See 2 more Smart Citations